Differences in dietary patterns between native and immigrant populations in Spain. - Joaquín Moncho; Lauren Elena Ortega Sarabia; Eva María Trescastro-López; Alba Martínez-García (PLoS ONE)
Background Migration in Spain has increased in recent decades, leading to a multicultural society. These migrations have brought about a transcendental change in the lifestyles and health of migrants. The aim of these study was to describe the frequency of consumption of sugary drinks, fruit and vegetables in the native and immigrant population residing in the Valencian Community (Spain) and its possible relationship with certain socioeconomic characteristics and lifestyles. Methods A representative sample of the population aged 15 years or older, non-institutionalised and resident in the Valencian Community. Descriptive cross-sectional observational study conducted on the basis of the Valencian Community Adult Health Survey, 2016. We analysed the consumption of fruit, vegetables and sugary soft drinks by country of birth and sex, and their possible association with socio-demographic characteristics and lifestyles. Results 5485 adults aged 15 years and older were analysed, 13.48% of whom were of immigrant origin. Overall, women had a significantly lower adjusted risk of inadequate vegetable consumption and lower than recommended fruit consumption. Men of immigrant origin showed a higher risk of lower than recommended vegetable consumption and a lower risk of inadequate consumption of sugar-sweetened soft drinks than natives. Women of immigrant origin showed a lower risk of lower-than-recommended vegetable consumption but a higher risk of inadequate consumption of sugar-sweetened soft drinks. Differences were also observed in the recommended consumption of these products according to educational level, social class, age, employment status, physical exercise and self-perceived weight. Conclusions Public health policies and interventions should incorporate a population-based approach that takes into account the origin of the population and addresses social and economic inequalities, with an emphasis on the most at-risk groups.